2007
DOI: 10.1111/j.1365-2036.2007.03268.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication reduced the incidence of gastric cancer, especially of the intestinal type

Abstract: SUMMARY BackgroundAlthough Helicobacter pylori infection is closely associated with gastric cancer development, follow-up studies after H. pylori eradication are still scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
86
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 26 publications
3
86
1
3
Order By: Relevance
“…However, many of these included cases whose cancer lesions developed relatively soon after eradication, namely within 2 years after the treatment (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many of these included cases whose cancer lesions developed relatively soon after eradication, namely within 2 years after the treatment (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports that showed the incidence and characteristic features of gastric cancer after H. pylori eradication (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008;Yanaoka et al 2009;de Vries et al 2009). However, many of these included cases whose cancer lesions developed relatively soon after eradication, namely within 2 years after the treatment (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 H. pylori eradication thus appears to be the most promising approach for the control of gastric cancer development, and the results of animal experiments have revealed that eradication of H. pylori, especially in the early stage, is effective for preventing stomach carcinogenesis. [4][5][6] However, current data indicate that H. pylori eradication does not lead to complete eradication of gastric cancer [7][8][9][10][11][12] and might be effective only in subjects without chronic atrophic gastritis (CAG) together with intestinal metaplasia. 7,10 Moreover, patients with extensive intestinal metaplasia-that is, metaplastic gastritis-should not be treated with eradication therapy, as bacterial load decreases with the progression of intestinal metaplasia, eventually resulting in spontaneous eradication.…”
mentioning
confidence: 99%
“…Including the reports by Yamamoto et al [1] and Matsuo et al [2], [10 studies of GC detected after Hp eradication have been published to date [3][4][5][6][7][8][9][10]. The characteristics of post-eradication GC include: (a) detection *40 months after eradication; (b) lesions are histologically well differentiated; (c) gross lesion morphology is depressed; and (d) the lesions are small (10-20 mm diameter).…”
mentioning
confidence: 99%